ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN BERDASARKAN RASIO PROFITABILITAS DAN RASIO SOLVABILITAS PADA PT INDOFOOD SUKSES MAKMUR TBK - Lubis, Nesa Lestari (Jurnal Budgeting, 2024)
This study is entitled Analysis of Financial Statements in Measuring Financial Performance Based on Profitability Ratios and Solvency Ratios at PT Indofood Sukses Makmur Tbk for the 2019-2023 Period. This study aims to determine the financial performance of PT Indofood Sukses Makmur Tbk as measured using the Profitability Ratio (return on assets), (return on equity), (net profit margin), and Solvency Ratio (debt to asset ratio), (debt to equity ratio). The data used in this study are the financial statements of PT Indofood Sukses Makmur Tbk for 2019-2023. The data analysis method in this research is descriptive statistics. The data type used is secondary data and the data collection technique used is documentation. The results showed that financial performance based on profitability and solvency ratios was not good. This can be seen from the calculation results which show that the profitability ratio and solvency ratio are below the industry average standard. This is because the company is less able to optimize the resources owned by the company